A note on site fidelity of marine tucuxis (Sotalia fluviatilis) in Guanabara Bay, southeastern Brazil - Azevedo , Alexandre de Freitas; Lailson-Brito Jr. , Jose; Cunha , Haydee A.; Sluys , Monique Van (J. Cetacean Res. Manage., 2023)
Since 1995, photo-identification techniques have been used to study the marine tucuxis (Sotalia fluviatilis) found in Guanabara Bay (22°50’S, 43°10’W), southeastern Brazil. The bay is surrounded by a metropolitan complex and is the most degraded area of this species’ distribution. From May 1995 to June 2003, 47 photo-identification boat surveys were conducted in the bay. Sixty-nine individuals were identified and catalogued. The results indicate that individual tucuxis have high site fidelity in Guanabara Bay. On average, dolphins were seen for 4.5 consecutive years, with a range of 1 to 8 years. Additionally, calves have remained in the area beyond sexual maturity. Guanabara Bay provides food and breeding grounds for this dolphin population, despite its high degree of degradation. The fact that such a small dolphin population, composed of resident individuals, depends on such a degraded area may pose serious problems for its conservation.